Sea monsters a prehistoric adventure : 3-D - Phillips, Sean MacLeod; Schreiber, Liev; Hoffman, Jerry, actor; Hunter, Cheryl, actress (Washington, D.C. : National Geographic, 2009)
Using CGI and dramatic reenactments, the film follows the life of a prehistoric reptile (Dolichorhynchops) during the Late Cretaceous period and its discovery in 1900 by Kansas teen George Sternberg.
Originally released as a motion picture in IMAX and other specialty theaters in 2007.
Features: interactive timeline, 3-D glasses.
Narrator: Liev Schreiber ; reenactors: Jerry Hoffman, Cheryl Hunter, Doug Kisgen.
Not rated.
Blu-ray disc, Dolby digital surround.
This is a Blu-ray disc which can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Plesiosaurus; Marine animals, Fossil; Animals, Fossil; Paleontology; Documentary films; 3-D films; Computer animation films; Nonfiction films; Feature films; Nature films; Science films